Heterostructure Engineering of a Reverse Water Gas Shift Photocatalyst. Issue 22 (4th October 2019) - Wang, Hong; Jia, Jia; Wang, Lu; Butler, Keith; Song, Rui; Casillas, Gilberto; He, Le; Kherani, Nazir P.; Perovic, Doug D.; Jing, Liqiang; Walsh, Aron; Dittmeyer, Roland; et al.
Abstract: To achieve substantial reductions in CO2 emissions, catalysts for the photoreduction of CO2 into value‐added chemicals and fuels will most likely be at the heart of key renewable‐energy technologies. Despite tremendous efforts, developing highly active and selective CO2 reduction photocatalysts remains a great challenge. Herein, a metal oxide heterostructure engineering strategy that enables the gas‐phase, photocatalytic, heterogeneous hydrogenation of CO2 to CO with high performance metrics (i.e., the conversion rate of CO2 to CO reached as high as 1400 µmol g cat −1 h −1 ) is reported. The catalyst is comprised of indium oxide nanocrystals, In2 O3− x (OH) y, nucleated and grown on the surface of niobium pentoxide (Nb2 O5 ) nanorods. The heterostructure between In2 O3− x (OH) y nanocrystals and the Nb2 O5 nanorod support increases the concentration of oxygen vacancies and prolongs excited state (electron and hole) lifetimes. Together, these effects result in a dramatically improved photocatalytic performance compared to the isolated In2 O3− x (OH) y material. The defect optimized heterostructure exhibits a 44‐fold higher conversion rate than pristine In2 O3− x (OH) y . It also exhibits selective conversion of CO2 to CO as well as long‐term operational stability. Abstract : A heterostructure strategy involving two nanostructured metal oxide semiconductors is introduced to provide a new kind of highly efficient and stable photocatalyst for converting gaseous CO2 to CO.